The effect of post mastectomy radiation therapy on survival in breast cancer patients with N1mic disease. (June 2020) - Patel, Mausam; Li, Chenghui; Aronson, Julia H.; Howie, Cole M.; Maraboyina, Sanjay; Prabhu, Arpan V.; Kim, Thomas
Abstract: Background: The role of post mastectomy radiation therapy (PMRT) in patients with N1mic breast cancer has not been well defined. A retrospective analysis was performed using the SEER database to evaluate the impact of PMRT on survival in patients with N1mic breast cancer. Materials and methods: Women with T1-T2, N1mic, M0 breast cancer who had undergone mastectomy were analyzed. Descriptive statistics were calculated for all variables. Univariate analysis to assess for differences in survival with respect to covariates was performed using the log rank test while multivariate analysis was performed with Cox proportional hazards regression. Sub-cohort analysis with propensity score matching was used to assess differences in survival among patients undergoing PMRT vs no PMRT. Comparisons were considered statistically significant at P < 0.05. Results: Among 5878 patients, 1202 (20%) underwent PMRT. On univariate analysis, PMRT was a significant predictor of CSS, but not OS. There was no difference in either OS or CSS between the PMRT vs no PMRT groups on multivariate Cox regression analysis and after propensity score matching. Conclusions: Among patients with T1-T2, N1mic, M0 breast IDC from the SEER database, there was no difference in either OS or CSS among patients who underwent PMRT vs no PMRT. These results suggest that PMRT does not impact survival among breast cancer patients with N1mic disease. However, additional prospective studies with longer follow up are necessary for further evaluation. Highlights: In women with N1mic breast cancer, there was no difference in overall survival with or without adjuvant radiation. CSS was worse among women undergoing adjuvant radiation on univariate analysis, but not on multivariate analysis. After propensity score matching, no significant difference was observed in survival between women undergoing PMRT vs no PMRT.